PENDEKATAN PENTA HELIX BERBASIS KEARIFAN LOKAL TERHADAP PENINGKATAN PENGGUNAAN TABLET TAMBAH DARAH (TTD) SEBAGAI PENCEGAHAN STUNTING DI KABUPATEN TAPANULI SELATAN - Ummi Irmadani Harahap; Efrida Yanti (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2025)
Stunting remains a major issue in South Tapanuli (15.6% in 2023). One direct cause is anemia from iron deficiency, linked to low adherence of pregnant women to iron–folic acid (IFA) tablets due to limited knowledge and negative attitudes.This study aims to explore the effect of a penta helix approach based on local wisdom on improving pregnant women’s use of iron tablets to help prevent stunting. Research method: This is a quantitative study using a pre-experimental design, specifically the one-group pretest-posttest design, as the goal is to compare pretest and posttest results within the intervention group. The sample was determined using purposive sampling, consisting of 60 pregnant women from the working areas of Pargarutan and Simarpinggan Health Centers, South Tapanuli Regency. Results: The findings of this study demonstrate a significant influence of the penta helix approach on enhancing knowledge, attitudes, and compliance with IFA among pregnant women as a preventive measure against stunting in South Tapanuli Regency. This is supported by the results of statistical analysis, which yielded a p-value of 0.001 (p < 0.005), indicating a statistically significant relationship. Conclusion: The penta helix approach has an effect on improving knowledge, attitudes, and compliance with IFA use among pregnant women to prevent stunting in South Tapanuli Regency.